Exploring The Role of Artificial Intelligence in Library Management at Public Primary School - Lestari, Dwi Makarti Amrih; Saryanto, Saryanto; Rejokirono, Rejokirono (Malikussaleh University, Aceh, Indonesia, 2025)
The rapid development of technology has brought significant changes in various areas of life, including the world of education. AI is a rapidly developing technology with enormous potential to improve the efficiency and effectiveness of resource management. Library management, which plays a crucial role in supporting teaching and learning activities in schools, employs AI in education. However, the increasing challenges in managing collections, the demand for rapid and accurate services, and the need for effective data management have increased the need for innovation in library management. This study aimed to explore the application of artificial intelligence (AI) in library management at SDN Piyaman 2 Wonosari, emphasizing enhancing operational efficiency, accessibility, and service quality. This study employs a qualitative descriptive approach, collecting data through interviews, observations, and questionnaires from students, teachers, and library staff. The researchers will then process, analyze, and discuss the collected data to conclude. The study results indicate that using artificial intelligence (AI) can improve library operational efficiency by reducing borrowing time, returning each book, and searching from five minutes to one minute. In addition, AI also increases user satisfaction, with an average increase from 60% to 85%. Despite the technical challenges and user adjustments, the results of this study indicate that AI has enormous potential to improve the effectiveness and efficiency of school libraries. Other schools can use this study as a model to implement AI technology in library management, making it more modern and responsive to user needs.